2020
DOI: 10.3390/ani10060957
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Concentrate-to-Forage Ratio Diets on Rumen Bacterial Microbiota and the Structures of Holstein Cows during the Feeding Cycle

Abstract: The objectives of this study were to investigate the ruminal bacterial changes during the feeding cycle. Six ruminally cannulated Holstein cows were used in this experiment. The high-forage (HF) and high-concentrate (HC) diets contained 70% and 30% dietary forage, respectively. Dairy cows were fed their respective diets for at least 28 days, then samples were collected at 0, 2, 4, 9, 12, 16 and 20 h post-feeding. The results showed that pH, the concentration of (total volatile fatty acids) TVFAs and the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 49 publications
(63 reference statements)
4
24
0
Order By: Relevance
“…Firmicutes were not affected by the concentrate intake in this study, which could be, at least in part, because of the 18-h post-feeding sampling time. Previous studies have reported that Firmicutes were highest just before feeding and lowest ~12 h post feeding ( 42 ). It was reported that the ratio of F:B increased with a high energy diet ( 5 , 43 ).…”
Section: Discussionmentioning
confidence: 92%
“…Firmicutes were not affected by the concentrate intake in this study, which could be, at least in part, because of the 18-h post-feeding sampling time. Previous studies have reported that Firmicutes were highest just before feeding and lowest ~12 h post feeding ( 42 ). It was reported that the ratio of F:B increased with a high energy diet ( 5 , 43 ).…”
Section: Discussionmentioning
confidence: 92%
“…(2020) and Wang et al. (2020a, 2020b). Formalin‐fixed rumen, duodenum, jejunum, and ileum samples were dehydrated and embedded in paraffin, and then, cross‐sections of 5‐μm thickness were cut and stained with HE.…”
Section: Methodsmentioning
confidence: 95%
“…The low AS pH decreased the abundance of Ruminobacter ( Firmicutes ) in this current study. Wang et al ( 69 ) reported that the cow intake high-forage diets increased the ruminal Ruminobacter abundance. Mu et al ( 70 ) found that fed a high grain-diet induce cow SARA increased the abundance of Ruminobacter .…”
Section: Discussionmentioning
confidence: 99%